Expanding variationist sociolinguistic research in varieties of German - Stratton, James M.; Beaman, Karen V. (Linguist) (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This collection provides a broad account of variationist sociolinguistic research on varieties of German, with the goals to encourage greater geolinguistic diversity in the field and to expand our understanding of language variation and change. The book illustrates that incorporating a wider variety of language data in sociolinguistic studies provides a broader, more holistic picture of variation and change. On the one hand, the book examines how variationist methods can contribute to the study of varieties of German, with each chapter following the principles of variationist sociolinguistics. On the other hand, the chapters examine how both intra- and extra-linguistic factors can influence variation and change. The volume also seeks to provide a broader understanding of German variation and change across time and space. The book highlights how the study of varieties of German through a variationist lens can offer new insights into language change more broadly, with applications for further research to other languages. This volume will be of most interest to scholars in language change, sociolinguistics, dialectology, and historical linguistics"--
Keywords: German language -- Variation; German language -- Dialects; German language -- Social aspects; Linguistic change; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics